Biologic Evaluation of the Azoxystrobin to control Pyricularia oryzae Cav. and Cercospora oryzae Miyake in crop of rice in Veracruz, Mexico. - Becerra, Enrique (2006)
In the state of Veracruz, Mexico, around 22000 ha of rice are sown annually; the average of yield is about 3.5 t/ha and it is mainly due to drought problems, which favours the presence of the fungi Pyricularia oryzae Cav. (rice blast) and Cercospora oryzae Miyake (narrow spot). In order to know the behavior of new fungicides, the effectiveness of Azoxystrobin on the control of these fungi was evaluated. The experiment was established in the municipality of Tres Valles, Veracruz, at the beginning of the 1999 rainy season. Seed of the rice variety Milagro Filipino Depurado was used. The experimental design was a Randomized Complete Block design with four replications. The evaluated treatments were: Azoxystrobin at 0.2, 0.4 and 0.6 l/ha vs Tecto60 at 0.5 kg/ha and a non-treated control.These treatments were applied when the first symptoms of rice blast and/or narrow spot were noticed. Factors being evaluate were: incidence, number of lesions in 20 plants, intensity index, phytotoxicity and grain yield. Azoxystrobin controlled both diseases better than Tecto 60; on the other hand, rice plants treated with Tecto 60 had significantly less lesions than the non-treated plants. The best control of P. oryzae and C. oryzae and the highest grain yield (4432 kg/ha) were obtained when Azoxystrobin was applied at 0.6 l/ha, although a good control of both diseases was also attained at 0.2 and 0.4 l/ha. None of the fungicides caused toxicity to rice.